Atlas of human dental pulp cells at multiple spatial and temporal levels based on single-cell sequencing analysis - Ren, Huihui; Wen, Quan; Zhao, Qingxuan; Wang, Nan; Zhao, Yuming (Frontiers in Physiology, 2022)
The dental pulp plays a crucial role in the long-term maintenance of tooth function. The progress of endodontic treatment and pulp tissue regeneration engineering has made pulp regeneration therapy promising in clinical practice. However, the mechanisms of pulp regeneration and the role of dental stem cells in development and regeneration have not been fully elucidated. Bridging the gaps between clinical operation and basic research is urgently need. With the application of single cell sequencing technology in dental research, the landscapes of human dental pulp cells have begun to be outlined. However, the specific cellular heterogeneity of dental pulp cells, especially that of dental stem cells, at different spatial and temporal levels, is still unclear. In this study, we used single-cell RNA sequencing analysis of pulp samples at four different developmental stages and combined findings with immunohistochemical staining to explore the development of dental pulp and stem cells. The results revealed temporal changes in the proportion of pulp cells during development. For example, mononuclear phagocytes accounted for a higher proportion in early samples. Odontoblasts identified by DMP1 had higher expression of ion channel-related and neurodevelopment-related genes. Subpopulations were identified in fibroblasts, odontoblasts and mesenchymal stem cells. We identified a subclass of odontoblasts that express DGKI and RRBP1 present in early developmental samples. A population of earlier mesenchymal stem cells expressed the SEPTIN gene, which may have greater proliferative and differentiation potential. Furthermore, dental pulp stem cells can differentiate into two directions: mineralization and myogenesis. In summary, the specific cellular heterogeneity of dental pulp cells was revealed at different spatial and temporal levels. These findings may shed light on the mechanism of tooth development. The gene expression profile of developing pulp cells may help to select cells for regenerative engineering and improve the success of dental pulp regeneration.